TAP Block in Postoperative Analgesia, A First Time Clinical Trial In Bangladesh (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Background: In perioperative care, a reliable pain management is a vital appeal. Over recent years, Transversus Abdominis Plane (TAP) block is introduced as an important component of multimodal analgesia.Objective: To evaluate efficacy of TAP block in postoperative analgesia for Total Abdominal Hysterectomy (TAH) with subarachnoid block (SAB) in comparison of morphine consumption and VAS score.Methods: 60 patients were randomly allocated into 2 groups (TAP group-A & control group-B). Standard SAB was applied to all patients for elective TAH. Immediate after operation classical TAP block was performed through both Lumber Triangle Of Petit (LTOP) of group A patients. Both groups were placed in Post Anesthesia Care Unit (PACU), arranged a common standard postoperative analgesic regimen for all, observed periodically and documented it accordingly in pre-designed data sheet.Results: TAP block prolonged the mean time of 1st required I/V morphine (TAP vs control, mean±SD 271.23±40.34 vs 195.33±22.16 min., p=0.001HS). Morphine requirement was also reduced (17.4±5.4 vs 26.2±4.4 mg, p=0.001HS). Pain VAS scores at rest and movement were also reduced at all time period (p? 0.01 to 0.001). There was no complication attributed to the TAP block.Conclusion: TAP block provided considerably effective postoperative analgesia in first 24 hours after major abdominal surgery like TAH.Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 3-11